Architecture and development of BI solution on MS Dynamics AX 2012 platform - Eperješi, Vladimír; Pour, Jan; Hubáček, Filip; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2015)
This thesis deals with the analysis and design of business intelligence solution for the needs of reporting for Microsoft Dynamics AX 2012 platform. Solution includes development guidelines for possible development in future. In the first part of the thesis there is introduced ERP system MS Dynamics AX 2012 which serves as a data source for reports. The following sections analyze the data sources and the need for enterprise reporting. Significant part of thesis is the analysis and design of individual basic dimensions and indicators together with the proposal of data flows and architecture solution. In chapters 6-9 are described best practices for creating data warehouse through all the layers of development. In chapter 10 are unified guidelines for the development of different parts of solution such as dimensional OLAP cubes for case of additional customer requirements.
Vedoucí práce: Jan Pour
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses